Pursuing conception: a physician's experience with in-vitro fertilization. - McCall, M (1996)
Infertility is a common problem. Approximately one in seven North American couples will experience it, either by being unable to conceive after a year of trying or by experiencing recurrent miscarriages. A family physician outlines her experiences when being treated for infertility by in-vitro fertilization and embryo transfer.